P‐142: On the Equivalent Circuit Models of Flexible AMOLED On‐Cell Touch Panels. Issue 1 (29th May 2019) - Kang, Jiahao; Guan, Ximeng; Luo, Haojun; Gupta, Amit; Tsong, Tina; Lu, Ping; Wu, Tsung-Ta; Wang, Yu-Min; Wang, Shaowen; Yu, Eric Kai-Hsiang; Zhao, Jigang; Chen, Chao; et al.
Abstract : On‐cell touch (OCT) is one of the critical techniques for thickness reduction and thus flexibility improvement of flexible active‐matrix organic light‐emitting diode (AMOLED) displays. In this work, an equivalent circuit model is established in order to speed up the iteration of OCT designs as well as to understand the impacts of design and process variations. This work provides implications for the implementation of OCT and highlights the necessity of such a hybrid methodology in OCT design.